Discharge experiences of speech-language pathologists working in Cyprus and Greece - Kambanaros, Maria (My University, 2010)
Post-termination relationships are complex because the client may need additional services and it may be difficult to determine when the speech-language pathologist-client relationship is truly terminated. In my contribution to this scientific forum, discharge experiences from speech-language pathologists working in Cyprus and Greece will be explored in search of commonalities and differences in the way in which pathologists end therapy from different cultural perspectives. Within this context the personal impact on speech-language pathologists of the discharge process will be highlighted. Inherent in this process is how speech-language pathologists learn to hold their feelings, anxieties and reactions when communicating discharge to clients. Overall speech-language pathologists working in Cyprus and Greece experience similar emotional responses to positive and negative therapy endings as speech-language pathologists working in Australia. The major difference is that Cypriot and Greek therapists face serious limitations in moving their clients on after therapy has ended.
Keywords: Discharge; Speech therapy; Cyprus; Greece